2019
DOI: 10.1590/s1984-296120180088
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia spp. infection in domestic cats from Rio de Janeiro State, southeast Brazil

Abstract: Ehrlichiosis is caused by agents belonging to Ehrlichia genus. Despite the frequent reports on the serological and molecular detection of E. canis in dogs in Brazil, there is scant data on ehrlichiosis in brazilian cats. This study aimed at investigating the occurrence of Ehrlichia spp. in domestic cats from Greater Rio de Janeiro, and evaluating hematological changes associated with this rickettsial infection. We searched for IgG antibodies against E. canis on blood samples of 216 cats by Indirect Fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
6
2
Order By: Relevance
“…was 7.4% (12.3% (MG) and 6.6% (SP)). Previous studies conducted in Brazil reported molecular positivity ranging from 3.7% to 8% [7,16,17]. The present study showed, for the first time, the occurrence of 'Candidatus Anaplasma amazonensis' in cats and the first molecular detection of Anaplasma sp.…”
Section: Discussionsupporting
confidence: 68%
“…was 7.4% (12.3% (MG) and 6.6% (SP)). Previous studies conducted in Brazil reported molecular positivity ranging from 3.7% to 8% [7,16,17]. The present study showed, for the first time, the occurrence of 'Candidatus Anaplasma amazonensis' in cats and the first molecular detection of Anaplasma sp.…”
Section: Discussionsupporting
confidence: 68%
“…Of the 11 cats positive for Ehrlichia, two (one positive in PCR and another positive in IFAT) had hyperproteinemia, which has also been found in E. canis seropositive cats in Rio de Janeiro (GUIMARÃES et al, 2019). In fact, this finding may be attributed to the increase of gamma globulins concentration during the febrile stage and persistence during subclinical and chronic stages of monocytic canine ehrlichiosis (RISTIC & HOLLAND, 1993).…”
Section: Discussionmentioning
confidence: 93%
“…However, the occurrence of cross-reactivity with other Anaplasmataceae family agents cannot be ruled out (WEN et al, 1997;ORTUÑO et al, 2005). Ehrlichia canis-like DNA was also detected in domestic cats in Mato Grosso (BRAGA et al, 2014b), Mato Grosso do Sul (ANDRÉ et al, 2015), Rio Grande do Norte (ANDRÉ et al, 2017), and Rio de Janeiro (GUIMARÃES et al, 2019), and in wild felids maintained in captivity in the state of São Paulo and in the Federal District (ANDRÉ et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may increase the chances to encounter a sand fly in nature and acquire and/or transmit the parasite. More importantly, co-infections with other feline endemic pathogens including viruses (FIV, FeLV) ( 102 ), bacteria ( Mycoplasma haemofelis, Ehrlichia spp) ( 103 , 104 ) other protozoans ( Cytauxzoon spp.) ( 105 ), and, helminths (enteric or lung worms) ( 106 ) may lead to immunosuppression of the cats.…”
Section: Discussionmentioning
confidence: 99%